Waqf dan Sistem Ekonomi Berkelanjutan: Tinjauan Bibliometrik atas Penelitian dan Inovasi Global dalam Ekonomi Islam (2008-2025) - Dupi, Muhamad; Dhiya Ul Husaen, Fuad (Islamic Economics and Business Faculty of UIN Antasari, 2025)
The paper will discuss the development of the global research on waqf in the relationship with sustainable economic systems and Islamic economic innovation throughout the period 2008-2025. The primary aim of the research is to methodically tracer the research patterns, patterns of collaboration and themes that can place waqf as a strategic tool of sustainable development and Sustainable Development Goals (SDGs). This paper is a bibliometric study of 380 articles with Scopus indices, and the data was retrieved on August 2, 2025 using the visualization tool VOSviewer. The findings indicate that the number of studies devoted to the topic of waqf doubled in 2018, which suggests that the trend has moved toward viability-based and policy-demanding uses of the Islamic social finance. Geographically, Southeast Asia, especially Malaysia and Indonesia, and countries of the Middle East become the primary hub of the scholarly production, which is reinforced by the development of the international cooperation in academic affairs. At the institutional level, Malaysia and Indonesia have been identified as prime centers of the global research network through universities and specialized research centers and journal analysis has shown that there is a high degree of concentration of publications in few core outlets. Thematic analysis reveals that there are four broad groups of clusters, namely: (1) waqf and Islamic financial instruments in relation to the SDGs, (2) cash and productive waqf as a social welfare, (3) waqf and financial inclusion as an economic development, and (4) philanthropy and poverty alleviation. The originality of the current study is that it covers a long period of time in the world and presents clear bibliometric mapping on sustainability. The policy implications include the need to enhance the governing of waqf and the development of digital waqf, as well as sustainability-oriented and green waqf models. Thih article will discuss the development of the global research on waqf in the relationship with sustainable economic systems and Islamic economic innovation throughout the period 2008-2025. The primary aim of the research is to methodically tracer the research patterns, patterns of collaboration and themes that can place waqf as a strategic tool of sustainable development and Sustainable Development Goals (SDGs). This paper is a bibliometric study of 380 articles with Scopus indices, and the data was retrieved on August 2, 2025 using the visualization tool VOSviewer. The findings indicate that the number of studies devoted to the topic of waqf doubled in 2018, which suggests that the trend has moved toward viability-based and policy-demanding uses of the Islamic social finance. Geographically, Southeast Asia, especially Malaysia and Indonesia, and countries of the Middle East become the primary hub of the scholarly production, which is reinforced by the development of the international cooperation in academic affairs. At the institutional level, Malaysia and Indonesia have been identified as prime centers of the global research network through universities and specialized research centers and journal analysis has shown that there is a high degree of concentration of publications in few core outlets. Thematic analysis reveals that there are four broad groups of clusters, namely: (1) waqf and Islamic financial instruments in relation to the SDGs, (2) cash and productive waqf as a social welfare, (3) waqf and financial inclusion as an economic development, and (4) philanthropy and poverty alleviation. The originality of the current study is that it covers a long period of time in the world and presents clear bibliometric mapping on sustainability. The policy implications include the need to enhance the governing of waqf and the development of digital waqf, as well as sustainability-oriented and green waqf models. Artikel ini akan membahas perkembangan penelitian global tentang waqf dalam kaitannya dengan sistem ekonomi berkelanjutan dan inovasi ekonomi Islam selama periode 2008–2025. Tujuan utama penelitian ini adalah untuk secara sistematis melacak pola penelitian, pola kolaborasi, dan tema-tema yang dapat menempatkan waqf sebagai alat strategis untuk pembangunan berkelanjutan dan Tujuan Pembangunan Berkelanjutan (SDGs). Makalah ini merupakan studi bibliometrik terhadap 380 artikel yang terindeks di Scopus, dan data diperoleh pada 2 Agustus 2025 menggunakan alat visualisasi VOSviewer. Temuan menunjukkan bahwa jumlah studi yang didedikasikan untuk topik waqf meningkat dua kali lipat pada tahun 2018, yang menunjukkan bahwa tren telah bergeser ke arah penggunaan waqf yang berbasis kelayakan dan berorientasi kebijakan dalam keuangan sosial Islam. Secara geografis, Asia Tenggara, terutama Malaysia dan Indonesia, serta negara-negara Timur Tengah menjadi pusat utama produksi akademik, yang diperkuat oleh perkembangan kerja sama internasional dalam urusan akademik. Pada tingkat institusional, Malaysia dan Indonesia telah diidentifikasi sebagai pusat utama jaringan penelitian global melalui universitas dan pusat penelitian khusus, dan analisis jurnal menunjukkan bahwa terdapat tingkat konsentrasi yang tinggi dari publikasi di beberapa outlet inti. Analisis tematik mengungkapkan bahwa terdapat empat kelompok kluster utama, yaitu: (1) Waqf dan instrumen keuangan Islam dalam kaitannya dengan Tujuan Pembangunan Berkelanjutan (SDGs), (2) waqf tunai dan produktif sebagai bentuk kesejahteraan sosial, (3) waqf dan inklusi keuangan sebagai bagian dari pembangunan ekonomi, dan (4) filantropi dan pengentasan kemiskinan. Keunikan studi ini terletak pada cakupan periode waktu yang panjang di seluruh dunia dan penyajian peta bibliometrik yang jelas mengenai keberlanjutan. Implikasi kebijakan meliputi kebutuhan untuk meningkatkan pengelolaan waqf dan pengembangan waqf digital, serta model waqf yang berorientasi pada keberlanjutan dan ramah lingkungan.